2003
DOI: 10.4310/atmp.2003.v7.n6.a4
|View full text |Cite
|
Sign up to set email alerts
|

The Glueball Superpotential

Abstract: We compute glueball superpotentials for four-dimensional, N = 1 supersymmetric gauge theories, with arbitrary gauge groups and massive matter representations. This is done by perturbatively integrating out massive charged fields. The Feynman diagram computations simplify, and are related to the corresponding matrix model. This leads to a natural notion of "projection to planar diagrams" for arbitrary gauge groups and representations. We discuss a general ambiguity in the glueball superpotential W (S) for terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(88 citation statements)
references
References 57 publications
4
83
1
Order By: Relevance
“…This puzzle intrigued several papers [19,20,3,15,21,22,23,24]. In particular, in [20], it was found that although N c,i = 0, we cannot set S i = 0.…”
Section: The Work Of Ikrsvmentioning
confidence: 99%
“…This puzzle intrigued several papers [19,20,3,15,21,22,23,24]. In particular, in [20], it was found that although N c,i = 0, we cannot set S i = 0.…”
Section: The Work Of Ikrsvmentioning
confidence: 99%
“…The last expression has a finite M → 0 limit which is precisely equal to log(A/Λ 3 ) as desired. This "demonstration" only shows that we did not yet establish the exact rule for dealing with "classical" quantities like S ≡ W 2 and their functions, quite apart from the quantum effect discussed in [22]. These problems need further investigations.…”
Section: Non-gaussian Correctionsmentioning
confidence: 99%
“…One may then ask how the information about this multiplicity is encoded in four dimensions, if at all? To this end, it is worth recalling the resolution of a (perhaps) analogous puzzle that arises on compactification to 1+1D on a 2-torus (see also [17]). Since we are computing the index tr F (−1) F , one might anticipate that such an additional reduction should not affect the conclusions.…”
Section: On the Anomaly Multipletmentioning
confidence: 99%